Longitudinal monitoring of anti-saliva antibodies as markers of repellent efficacy against Phlebotomus perniciosus and Phlebotomus papatasi in dogs - Risueño, J; Spitzová, T; Bernal, L J; Muñoz, C; López, M C; Thomas, M C; Infante, J J; Volf, P; Berriatua, E (Medical and veterinary entomology, 2019)
A 2-year longitudinal study of enzyme-linked immunosorbent assay (ELISA) antibodies against Phlebotomus perniciosus and Phlebotomus papatasi (Diptera: Psychodidae) sandfly saliva was performed in 32 Beagle dogs treated preventively with an imidacloprid-permethrin topical insecticide in an endemic area in Spain. Dogs were grouped into three sandfly exposure groups according to the time of inclusion in the study. Assays analysed immunoglobulin G (IgG) against salivary gland homogenates (SGH) of both species and recombinant P. papatasi rSP32 and P. perniciosus rSP03B proteins in serum. The dogs were participating in a Leishmania infantum (Kinetoplastida: Trypanosomatidae) vaccine trial and were experimentally infected with the parasite in the second year. No dog acquired natural L. infantum infections during the first year, but most developed anti-saliva antibodies, and median log-transformed optical densities (LODs) were seasonal, mimicking those of local sandflies. This indicates that the repellent efficacy of the insecticide used is below 100%. Multi-level modelling of LODs revealed variability among dogs, autocorrelation and differences according to the salivary antigen and the dog's age. However, dog seroprevalence, estimated using pre-exposure LODs as cut-offs, was relatively low. This, and the fact that dogs did not become naturally infected with L. infantum, would support the efficacy and usefulness of this imidacloprid-permethrin topical insecticide in canine leishmaniasis control.
Keywords: longitudinální studie; antigens; saliva; Antibodies; psi; protilátky; permethrin; Insect Repellents; Dogs; repelenty proti hmyzu; Permethrin; Phlebotomus; Španělsko; ženské pohlaví; zvířata; Spain; dogs; neonikotinoidy; biologické markery; Insect Bites and Stings; kousnutí a bodnutí hmyzem; Neonicotinoids; Longitudinal Studies; Biomarkers; Nitro Compounds; dusíkaté sloučeniny; Female; insecticides; sandfly; Animals